2(3x+4)=2(4x+1)

Simple and best practice solution for 2(3x+4)=2(4x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x+4)=2(4x+1) equation:


Simplifying
2(3x + 4) = 2(4x + 1)

Reorder the terms:
2(4 + 3x) = 2(4x + 1)
(4 * 2 + 3x * 2) = 2(4x + 1)
(8 + 6x) = 2(4x + 1)

Reorder the terms:
8 + 6x = 2(1 + 4x)
8 + 6x = (1 * 2 + 4x * 2)
8 + 6x = (2 + 8x)

Solving
8 + 6x = 2 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
8 + 6x + -8x = 2 + 8x + -8x

Combine like terms: 6x + -8x = -2x
8 + -2x = 2 + 8x + -8x

Combine like terms: 8x + -8x = 0
8 + -2x = 2 + 0
8 + -2x = 2

Add '-8' to each side of the equation.
8 + -8 + -2x = 2 + -8

Combine like terms: 8 + -8 = 0
0 + -2x = 2 + -8
-2x = 2 + -8

Combine like terms: 2 + -8 = -6
-2x = -6

Divide each side by '-2'.
x = 3

Simplifying
x = 3

See similar equations:

| 4x^3+15x^2+37x+39=0 | | 3-2k=-9 | | 8v-10=105 | | (x+1)(x-7)=0 | | 8r^2-12r=0 | | 0=-16x^2+3x+1.3 | | 3x^2+34x+80=0 | | 18=3(d-1) | | 3-4(x+2)=15 | | x^3+x^2-x-1.7=0 | | 3a-32=-2a+23 | | 7(-6y+9)+4y=-13 | | (x*x)+(x*x)=36 | | 137-4x=23x+23 | | 20.4-2c=5 | | 4x+y+1=-y-2x+3 | | (a-b)(a^2+2ab+b^2)= | | 12y^2+2y=0 | | (2c-d)(2c^2+2cd+d^2)= | | 7-7x=29-21x | | 3x+10+x+2=2x+20 | | -3x+7=28 | | 3x-45=6 | | 7(n+6)+8(n+4)= | | 8(x+3)+14(x+2)=74 | | 3(6z-1)-4(z+9)=4(z+1) | | 0.02-2.6=5.38 | | p=3a+5b | | 4x-12=x+6 | | 5b*6b= | | 3x*5x*2x= | | 6(2z-1)-2(z+3)=3(z+1) |

Equations solver categories